Fostering teacher organizational citizenship behavior in Indonesia: the roles of local wisdom, organizational climate, and motivated mediation - Ade Suherlan; Iyan Irdiyansyah; Sri Setyaningsih (Jurnal Konseling dan Pendidikan, 2025)
The objective of this study is to develop a constellation model illustrating the influence among variables to enhance teachers' Organizational Citizenship Behavior (OCB) by employing the POP-SDM. Mixed method is used to conduct this study. The population of the study are the vocation high school teachers in Bogor Regency. As much as 218 are chosen randomly using multistage random sampling.  Interview, documentation and questionnaire are used to collect the data. Interview and documentation are used to gain qualitative data, and the rest is used to gain quantitative data. SEM PLS is used as statistical analysis to find the quantitative result. The resulting model has significant relevance, especially in understanding the dynamics of educational organizations in Indonesia. As an implication, if teachers' OCB is to be improved, it is necessary to strengthen religiosity, mutual cooperation, organizational climate and tolerance as exogenous variables with work motivation as an intervening variable. This relevance lies in several important aspects that are at the core of the inter-variable influence, namely religiosity, mutual cooperation, organizational climate, tolerance, and motivation.